City Branding Kota Bandung through Bandung Tour on Bus - Maylanny 081224388033 Christin (Universitas Muhammadiyah Yogyakarta, 2015)
Bandung is one of the world's tourism city has been established on 25 September 2013 in Beijing by UNESCO. To meet one of the index in order to become a tourism city of the world, in it there is an aspect of city tour. Therefore, the Government of the Bandung city to make innovation a new city tour bus named Bandung Tour On a Bus or a usually called Bandros. The theory used in this research is city branding (Anholt 2006) and a communication strategy (Arifin in Abdullah, 2009). To uncover these issues, this research uses qualitative research types that serve to gain a deeper understanding of common, overarching performance management against the bus bandros in the developing city of Bandung city branding through document that is descriptive, and use case studies to his approach with the aim of helping the audience understand what is being researched, a new interpretation, a new perspective, a new meaning.The results of this study expressed that bus bandros a pioneer of other cities in Indonesia in making city tour bus. Bus bandros can make the public curious about this transportation with the concept of the double decker. Communication strategy undertaken by the Organizer i.e. BP2KB is using social media twitter and instagram to spread information about reservations and schedule of activities. In addition, using whatsapp to be able to communicate with the passengers bus bandros.Starting from dotted this research, some suggestions that may be put forward for the tourism promotion agency of the city of Bandung, maximize media communication and in the dissemination of information. Social media is also better if managed by people who understand in their jobs. In addition, the community that the ascending bus bandros should be able to maintain existing public facilities and carry out all its activities in accordance with existing procedures. Keyword: City Branding, City Tour Bus, Communication Strategy.